Perpendicular Giant Magnetoresistance and Magnetic Properties of Co/Cu Nanowire Arrays Affected by Period Number and Copper Layer Thickness. (13th December 2016) - Han, Juan; Qin, Xiufang; Quan, Zhiyong; Wang, Lanfang; Xu, Xiaohong
Abstract : One-dimensional magnetic nanowires have attracted much attention in the last decades due to their unique physical properties and potential applications in magnetic recording and spintronics. In this work, ordered arrays of Co/Cu multilayered nanowires which can be exploited to develop magnetoresistive sensors were successfully prepared using porous anodic alumina (PAA) templates. The structure and morphology of the multilayered nanowire arrays were characterized by transmission electron microscopy and scanning electron microscopy. The nanowire arrays are highly ordered and the average diameter is about 50 nm, which is controlled by the pore diameter of the PAA templates. The influences of period number and Cu layer thickness on the magnetic and the giant magnetoresistance (GMR) properties were investigated. The coercivity and remanence ratio increase first and then gradually tend to be stable with the increase of period number and the Cu layer thickness, while the GMR ratio increases first and then decreases with the increase of the period number accompanied by an oscillatory behavior of GMR as the Cu layer thickness changes, which are ascribed to the spin dependence electron scattering in the multilayers. The optimum GMR of −13% appears at Co (50 nm)/Cu (5 nm) with 200 deposition cycles in our experimental conditions.